2015
DOI: 10.1124/jpet.114.220350
|View full text |Cite
|
Sign up to set email alerts
|

Four Cation-Selective Transporters Contribute to Apical Uptake and Accumulation of Metformin in Caco-2 Cell Monolayers

Abstract: Metformin is the frontline therapy for type II diabetes mellitus. The oral bioavailability of metformin is unexpectedly high, between 40 and 60%, given its hydrophilicity and positive charge at all physiologic pH values. Previous studies in Caco-2 cell monolayers, a cellular model of the human intestinal epithelium, showed that during absorptive transport metformin is taken up into the cells via transporters in the apical (AP) membrane; however, predominant transport to the basolateral (BL) side occurs via the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
123
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 39 publications
2
123
2
Order By: Relevance
“…A recently published study demonstrated that the human serotonin transporter (SERT, SLC6A4) transports metformin and suggested that it plays a role in metformin intestinal absorption. 14 However, we did not observe significant metformin uptake in the overexpressing human SERT cell line (gift from Dr. Randy Blakely) though robust uptake of serotonin was observed (Figure SP-4B). We also did not observe significant metformin uptake in HEK cells transiently transfected with the cDNA of SLC6A4 (SERT), however significant metformin uptake was observed in HEK cells transiently transfected with the cDNAs of SLC22A1 and SLC19A3 (Figure SP-4C).…”
Section: Discussionmentioning
confidence: 71%
“…A recently published study demonstrated that the human serotonin transporter (SERT, SLC6A4) transports metformin and suggested that it plays a role in metformin intestinal absorption. 14 However, we did not observe significant metformin uptake in the overexpressing human SERT cell line (gift from Dr. Randy Blakely) though robust uptake of serotonin was observed (Figure SP-4B). We also did not observe significant metformin uptake in HEK cells transiently transfected with the cDNA of SLC6A4 (SERT), however significant metformin uptake was observed in HEK cells transiently transfected with the cDNAs of SLC22A1 and SLC19A3 (Figure SP-4C).…”
Section: Discussionmentioning
confidence: 71%
“…In addition to effects mediated by the microbiome, the gut mucosal cells of the host organism are exposed to the high gut levels of these drugs, and multiple studies indicate significant accumulations of metformin 18, 19, 83, 84 and phenformin 85, 86 . Further, these cells are reported to have limited ability to reduce folate 87 .…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others have shown that the organic cation transporters, OCT1 and OCT3, as well as the serotonin transporter, SERT, play a role in the uptake of serotonin and histamine as well as metformin [20, 22, 61]. In the intestine, these transporters appear to be involved in the influx of their substrates from the lumen into the intestinal epithelial cells or transport between the blood and intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…DAO transcript levels are the highest among the four genes in the stomach, duodenum, small intestine and colon, followed by SERT, which has greater mRNA expression levels in the small intestine, as compared to OCT1 and OCT3 (Supplemental Table 1). Although transcript levels of both OCT1 and OCT3 are low in intestinal tissue, the protein expression of OCT1, OCT3 and DAO are medium to high, depending on the location in the intestine (Supplemental Table 1) [28, 52, 61]. Based on the localization of these transporters (Fig.…”
Section: Discussionmentioning
confidence: 99%